ANALYSIS OF THE NEEDS FOR SCIENCE LEARNING MEDIA FROM TEACHER’S PERSPECTIVE IN ORDER TO IMPROVE STUDENT’S INTEREST IN SCIENCE LEARNING - Amalia Intan Sari; Sisri Febrina Ningsih (SEMESTA: Journal of Science Education and Teaching, 2022)
Learning media, namely acting as a mediator of information between the source (teacher) and the recipient (student), is one of the resources that can assist teachers in offering simpler and more effective learning materials (student). The goal of this study is to identify and evaluate the media that teachers in SMPN 30 Padang and the SMP Development Laboratory at Padang State University use to engage students in the science learning process. Analyzing the information from the learning material employed was another goal of this study. This form of research, which aims to examine the needs of learning media, is qualitative descriptive research. Science instructors from SMPN 30 Padang and SMP Pembangunan Laboratorium in Padang City served as the study's participants. Based on the research data, it is known that there are differences in the use of instructional media between the two schools, where in SMPN 30 Padang the use of instructional media is better than SMP Pembangunan Laboratorium.